EXISTENTIAL DIMENSIONS OF WAR IN CONTEMPORARY UKRAINIAN POETRY - Reha, Danylo (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2026)
Abstract. The article is devoted to the analysis of the existential dimensions of war in contemporary Ukrainian poetry, created in the context of the full-scale Russian invasion. The theoretical basis is the concepts of K. Jaspers, M. Heidegger, A. Camus and J.-P. Sartre, which allow us to comprehend poetic texts through the prism of limit situations, absurdity, freedom, anxiety and existential rebellion. The study examines works from the anthology “The Word Tempered by War. Volume 1”, which demonstrate a wide spectrum of war experience — from the immediate limitlessness caused by war to internal psychic trauma, from the destruction of human integrity to its sustainable restoration. The analysis showed that the key existential dimensions in war poetry are manifested in the forms of experiencing death, fear and anxiety, in expressions of internal and moral rebellion, in the themes of freedom and choice despite impossible conditions, in the temporal discontinuity of being, in silence as a way of testimony, in the ethical encounter with the Other, in the search for meaning and the possibility of transcendence. The article demonstrates that modern Ukrainian war poetry acts not only as an artistic response to a historical catastrophe, but also as a form of existential self-awareness and the preservation of human dignity in conditions of radical evil.